Cutting COF‐like C4N to Give Colloidal Quantum Dots: Towards Optical Encryption and Bidirectional Sulfur Chemistry via Functional Group and Edge Effects. Issue 8 (3rd January 2022) - Shu, Chenhao; Fang, Long; Yang, Meijia; Zhong, Linfeng; Chen, Xiaochuan; Yu, Dingshan
Abstract: Herein, we report the first synthesis of colloidal C4 N quantum dots (QDs) and their functional composites and explore their optical activities and edge‐selective polysulfide adsorption‐catalysis. As‐obtained C4 NQDs are rich in carbonyl groups and edges, allowing good solution processability and facile assembly with other moieties for creating functionalities. While C4 NQDs show normal fluorescence (FL), the QD/poly(vinyl alcohol) (PVA) composites give FL/room‐temperature‐phosphorescence (RTP) dual‐mode emission, enabling the corresponding solution to be used as an encryption ink. The QDs anchored onto carbon nanotubes can be used as a barrier layer to decorate commercial separators, endowing a Li−S cell with excellent cycling stability, high rate capability, and large areal capacity. Computation and experiment studies show that edge sites in C4 N favor polysulfide adsorption and catalysis and the enriched edges and carbonyl groups in QDs synergically promotecatalytic conversion of sulfur species. Abstract : A new class of colloidal carbon‐nitride‐like quantum dots, C4 NQDs, and their functional composites have been introduced. They show interesting fluorescence/room‐temperature‐phosphorescence dual‐mode emission for advanced optical encryption. They also show edge‐selective adsorption‐catalysis toward sulfur chemistry in Li−S cells by exploiting the functional group and edge effects of quantum dots.